2020
DOI: 10.3389/fonc.2020.00217
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib Inhibits Cell Proliferation and Induces Autophagy in Human Papillary Thyroid Carcinoma via the PI3K/Akt/mTOR Signaling Pathway

Abstract: Background: Patients with metastatic radioiodine-refractory papillary thyroid carcinoma (PTC) have limited treatment options and a poor prognosis. There is an urgent need to develop new drugs targeting PTC for clinical application. Apatinib, a novel small-molecule tyrosine kinase inhibitor (TKI), is highly selective for vascular endothelial growth factor receptor-2 (VEGFR2) and exhibits antitumor effects in a variety of solid tumors. Although apatinib has been shown to be safe and efficacious in radioiodine-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 25 publications
(26 reference statements)
5
28
0
1
Order By: Relevance
“…In order to investigate the potential mechanism underlying the effect of apatinib, the study further analyzed the apatinibtreated cells and xenograft tumor tissues. The results revealed a decrease in the expression of p-ERK1/2 and p-AKT consistent with their behavior in thyroid cancer (27), gastric cancer (28), ovarian cancer (29), cholangiocarcinoma (22) and neuroblastoma (30). Previous research also showed that KRAS mutations appeared in 90% of pancreatic cancer patients (31), while RAS-stimulated ERK1/2/MAPK and PI3K/AKT were reported to be active in various pancreatic cancer models (32).…”
Section: Discussionsupporting
confidence: 66%
“…In order to investigate the potential mechanism underlying the effect of apatinib, the study further analyzed the apatinibtreated cells and xenograft tumor tissues. The results revealed a decrease in the expression of p-ERK1/2 and p-AKT consistent with their behavior in thyroid cancer (27), gastric cancer (28), ovarian cancer (29), cholangiocarcinoma (22) and neuroblastoma (30). Previous research also showed that KRAS mutations appeared in 90% of pancreatic cancer patients (31), while RAS-stimulated ERK1/2/MAPK and PI3K/AKT were reported to be active in various pancreatic cancer models (32).…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, some novel drugs were utilized to TC therapy. For example, apatinib could induce apoptosis and autophagy of PTC cells through PI3K/Akt/ mTOR signaling pathway [60]. Previous studies have indicated that emodin inhibited the angiogenesis and metastasis of ATC by regulating TRAF6-mediated pathways, including the TRAF6/CD147/MMP9 pathway [47].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported that apatinib inhibited the proliferation, migration and invasion of cholangiocarcinoma cells [ 35 ]. Meng et al found that apatinib inhibited cell proliferation and induced autophagy in human papillary thyroid carcinoma [ 36 ]. Xu et al proved that apatinib enhanced the chemosensitivity of gastric cancer cells to paclitaxel and 5-fluorouracil [ 37 ].…”
Section: Discussionmentioning
confidence: 99%